Post liposuction Mycobacterium abscessus surgical site infection in a returned medical tourist complicated by a paradoxical reaction during treatment - Siong H. Hui; Lisa Noonan; Ruchir Chavada (MDPI AG, 2015)
Rapidly growing mycobacterial skin and soft tissue infections are known to complicate cosmetic surgical procedures. Treatment consists of more surgery and prolonged antibiotic therapy guided by drug susceptibility testing. Paradoxical reactions occurring during antibiotic therapy can further complicate treatment of non-tuberculous mycobacterial infections. We report a case of post liposuction Mycobacterium abscessus surgical site infection in a returned medical tourist and occurrence of paradox during treatment.